Population performance of Tetranychus evansi (Acari: Tetranychidae) on African tomato varieties and wild tomato genotypes - Savi, P. J. [UNESP]; Moraes, G. J. de; Melville, C. C. [UNESP]; Andrade, D. J. [UNESP] (Springer, 2019)
The tomato red spider mite, Tetranychus evansi Baker & Pritchard, is one of the main pests of the tomato crop in several countries, mainly in Africa, where it can reduce tomato yield by up to 90%. The biotic potential of this mite is high and its control is difficult because of low efficiency of chemicals used and the rapid development of resistance to acaricides. We used the two-sex life table to evaluate the effect of two wild tomato genotypes (PI134417 and PI134418) and five tomato varieties widely grown in Benin (Kekefo, Akikon, TLCV15, Tounvi, and TOML4) on demographic characteristics of T. evansi under laboratory conditions. Tetranychus evansi did not develop on the genotypes PI134417 and PI134418, indicating their resistance to this mite. Developmental time of immature stages and female longevity were significantly higher on TLCV15 and Kekefo. Fecundity, net reproductive rate (R-0), intrinsic rate of increase (r), and finite rate of increase () of T. evansi on the African varieties were not statistically different among varieties. Generation time (T) was shorter on TOML4 than on TLCV15 and Tounvi. Thus, efforts should be made to prospect varieties with resistance characteristics or to develop other control means, to reduce the use of pesticides to control T. evansi in Africa.
Keywords: Tomato red spider mite; Two-sex life table; Solanum lycopersicon; Plant resistance